Sport Metaphors in Political News Headlines - Hang, Nguyen Thi Thu (VNU Journal of Foreign Studies; Vol 32 No 2, 2016)
Abstract: The research paper is aimed at investigating sport metaphors in news headlines whose contents are related to politics, more specifically, in headlines of some electronic articles on theUS presidential election campaign 2012. By dint of exploring sport metaphors in such headlines, the study is expected to reveal sports whose language appears with high frequencies in political news as well as to uncover reasons underlying the mechanism of cognition in those sport metaphors. Some implications in translation are also mentioned at the end of the research paper. Keywords: Sport metaphors, political, news headlines.